2014
DOI: 10.1016/j.foodchem.2013.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Compositional differences in soybeans on the market: Glyphosate accumulates in Roundup Ready GM soybeans

Abstract: This article describes the nutrient and elemental composition, including residues of herbicides and pesticides, of 31 soybean batches from Iowa, USA. The soy samples were grouped into three different categories: (i) genetically modified, glyphosate-tolerant soy (GM-soy); (ii) unmodified soy cultivated using a conventional "chemical" cultivation regime; and (iii) unmodified soy cultivated using an organic cultivation regime. Organic soybeans showed the healthiest nutritional profile with more sugars, such as gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(236 citation statements)
references
References 27 publications
8
216
0
12
Order By: Relevance
“…Nonetheless, glyphosate residues were reported in bottled drinking water (Rendón-von Osten and Dzul-Caamal, 2017). Glyphosate residues were detected in honey and soy sauce (Rubio et al, 2014), in produce (Bøhn et al, 2014), processed food products, even in human specimens (blood, urine, mother's milk) (Knudsen et al, 2017;Rendón-von Osten and Dzul-Caamal, 2017). It should be noted, however, that measurements of glyphosate in complex biological matrices e.g., blood and breast milk, that led to positive scores used ELISA methods of questionable accuracy, and instrumental analysis by LC-MS/MS did not find glyphosate above its limit of detection in human breast milk (McGuire et al, 2016;Steinborn et al, 2016).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…Nonetheless, glyphosate residues were reported in bottled drinking water (Rendón-von Osten and Dzul-Caamal, 2017). Glyphosate residues were detected in honey and soy sauce (Rubio et al, 2014), in produce (Bøhn et al, 2014), processed food products, even in human specimens (blood, urine, mother's milk) (Knudsen et al, 2017;Rendón-von Osten and Dzul-Caamal, 2017). It should be noted, however, that measurements of glyphosate in complex biological matrices e.g., blood and breast milk, that led to positive scores used ELISA methods of questionable accuracy, and instrumental analysis by LC-MS/MS did not find glyphosate above its limit of detection in human breast milk (McGuire et al, 2016;Steinborn et al, 2016).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…Its use has grown significantly with the development of crops genetically engineered to tolerate the herbicide [14] in part because of the appearance of glyphosate-resistant weeds. "Triple-stacked" corn is a hybrid corn variety that expresses three transgenic events simultaneously in the same plant, including the following: 1) the CP4 EPSPS (5-enolpyruvulshikimate-3-phosphate synthase) protein that adds resistance to the herbicide glyphosate, 2) Cry1Ab protein to protect against European corn borer (Ostrinia nubilalis), and 3) Cry3Bb1 protein to protect against corn rootworm (Diabrotica spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Cuhra and co-workers tested chronic effects of glyphosate and Roundup and showed that environmental concentrations of 0.05-0.45 mg/l (active ingredient) cause negative effects on D. magna offspring size and reproduction (Cuhra et al 2013). Chemical residues of glyphosate and its primary metabolite, AMPA, are documented to be present in herbicide tolerant GM soy (Duke et al 2003;Bøhn et al 2014).…”
Section: The Daphnia Magna Modelmentioning
confidence: 99%
“…For details on use of agrochemicals by the farmers, soybean varieties grown, analyses of nutritional contents in the soybean and methods for analyzing chemical residues, see (Bøhn et al 2014).…”
Section: Soy Samples and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation